IMPORTANCE OF HUMAN CAPITAL AND ITS INFLUENCE ON THE SUCCESS OF CONTEMPORARY COMPANIES IN CDE - Rubén Ríos Ramírez, Hernán (Revista Gênero e Interdisciplinaridade, 2023)
To define human capital, we must talk about the economic value of the professional skills that a person has, capitalized in the value of the future benefits that a person expects to obtain with his work. and, that if the financial aspect is added, we can talk about obtaining the integral wealth of people, which is what really matters to all organizations, since with it productivity is obtained, as a result of work experience as well as the degree of their training. Through a mixed investigation, applying interviews and surveys to obtain the data on which the results were interpreted, in a single study with the objective of obtaining a broader panorama of the object of study, and that through a level Descriptively, the situation is presented, which in the particular case is the importance of human capital for the success of contemporary companies in Ciudad del Este. Based on the results, it can be determined that constant training is capitalized in greater productivity of human capital, which represents greater efficiency in their daily activities. It is concluded that these companies lack adequate tools with regard to HR, and therefore do not adequately execute their efforts, however, it has been verified that they apply internal recruitment for internal vacancy, and that none of them apply a performance evaluation. to the staff, precisely because of a continuous lack of training.